(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Nasopharyngeal Carcinoma (NPC) is uncommon in Iraq, but its incidence is raising due to increased exposure to diverse risk factors. Many of the NPC-related risk factors are becoming more and more apparent in Iraq. The exactly risk factors for nasopharyngeal carcinoma (NPC) in Anbar province, Iraq are not known. Objectives: To determine the association between Epstein- Barr virus (EBV) infections and other risk factors with the development NPC of Iraqi patients. Patients and Method: Sixty-seven paraffin-embedded tissues of NPC cases, 134 normal noncancerous nasopharyngeal biopsy samples, and tonsillectomy specimens from patients with chronic hypertrophic tonsillitis as controls were enrolled in the study that was conducted between 12 January 2012 and 21 January 2019. DNA of EBV was extracted from both controls and neoplastic tissues and analyzed by PCR technique using primers specific to EBV Latent Membrane Protein-1 Oncogene (LAMP-1) for the presence of EBV. A Questioners data form for all patients and controls were filled by the researchers regarding other risk factors of NPC including the patient’s age, sex, residence, radiation exposure, history of chronic rhinitis, family history of NPC, tobacco smoking, alcohol consumption, herbal medicines, tea consumption, exposure to formaldehyde and exposure to different inhalants. Results: The following risk factors were found to be independently associated with illness: EBV (adjusted odds ratio [OR] 7.852, 95% confidence interval [CI] 2.22–27.72), herbal medicine (OR 19.051, CI 7.56– 47.95) and Family history of NPC (OR 63.717, CI 6.67–607.96). Conclusion: Combination of family history of NPC , EBV exposure and herbal medicine was a strong risk factor for NPC.